2015
DOI: 10.1073/pnas.1504732112
|View full text |Cite
|
Sign up to set email alerts
|

Three types of rescue can avert extinction in a changing environment

Abstract: Setting aside high-quality large areas of habitat to protect threatened populations is becoming increasingly difficult as humans fragment and degrade the environment. Biologists and managers therefore must determine the best way to shepherd small populations through the dual challenges of reductions in both the number of individuals and genetic variability. By bringing in additional individuals, threatened populations can be increased in size (demographic rescue) or provided with variation to facilitate adapta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
189
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 160 publications
(211 citation statements)
references
References 45 publications
13
189
1
Order By: Relevance
“…Continual addition of captive‐bred birds would buffer the wild population against stochastic fluctuations, with positive outcomes for growth and persistence (Hufbauer et al . ). Although supplementation with captive‐bred cassidix resulted in positive population growth, supplementation of the cassidix population with gippslandicus (with or without captive‐bred cassidix ) had a stronger positive effect on genetic outcomes than supplementation with captive‐bred cassidix alone.…”
Section: Discussionmentioning
confidence: 97%
“…Continual addition of captive‐bred birds would buffer the wild population against stochastic fluctuations, with positive outcomes for growth and persistence (Hufbauer et al . ). Although supplementation with captive‐bred cassidix resulted in positive population growth, supplementation of the cassidix population with gippslandicus (with or without captive‐bred cassidix ) had a stronger positive effect on genetic outcomes than supplementation with captive‐bred cassidix alone.…”
Section: Discussionmentioning
confidence: 97%
“…Dispersal of individuals between sub-regions can rescue local populations from extinction both demographically and genetically [62,63]. Dispersal together with balancing selection in a spatially structured population may be sufficient to prevent a DMV [27].…”
Section: Discussionmentioning
confidence: 99%
“…This finding supported the multiple introductions documented in the importation history, and the notion that genetic admixture can increase genetic diversity (Rius & Darling, ). Furthermore, genetic admixture may be able to rescue populations that had small initial propagule size or underwent demographic bottlenecks (Hufbauer et al, ) Additionally, two out of the three populations of N. eichhorniae in South Africa demonstrated high allelic richness (>4) and FLOCK allocation tables found that one of these populations (SA: Kubusi River) had two genetic sources (Australia and USA: Florida). Interestingly, FLOCK analyses demonstrated that only one population from USA: Florida contributed to the genetic composition of SA: Wolseley, which also demonstrated high allelic richness.…”
Section: Discussionmentioning
confidence: 99%